Antimicrobial Evaluation of Dichloro Chromene Isoxazoles and Isoxazoline Derivatives - Ashutosh K. Dash; Nandan Sarkar; Nazar Hussain; Sabari Ghosal; Debaraj Mukherjee (To Chemistry Journal, 2019)
In the present study, the synthesized benzopyran isoxazolines and isoxazoles were evaluated for antibacterial activity by Agar well diffusion method against multi drug resistance (MDR) clinical isolates of five bacterial strains.i.e., Staphylococcus sp. (2413), Enterococcus sp. (2449), and Escherichia sp. (2461), Acinetobacter sp. (2457) and Serratia sp (2442). MIC (Minimum inhibitory concentration) and MBC (Minimum bactericidal concentration) of the potent derivatives were calculated and tabulated. A partial structure activity relationship (SAR) was done on the basis of microbial inhibition data. Compounds 3, 6, 8, 9, 11, 14 and 20 were the most promising antibacterial molecule. Compound 3, the precursor of isoxazole / isoxazoline found to be most active antibacterial candidate as well as bactericidal too.